Determinación de triglecéridos, colesterol total, HDL, LDL y su relación con la obesidad abdominal en choferes de la Cooperativa de Transporte Unión Cariamanga del cantón Loja - Apolo Bravo, Mariuxi Zoraida (2014)
Obesity and dyslipidaemia are complex and heterogeneous clinical pathologies with a strong genetic multifactorial component associated to the lifestyle; nowadays, these illnesses represent a big problem to the world public health. Because of that, this project was carry out in order to quantify the serum levels of Triglycerides, Total Cholesterol (HDL and LDL), to measure the abdominal perimeter and to associate the lipid profile to the central obesity of the drivers of the “Union Cariamanga” Transportation Cooperative of the city of Loja. Through a descriptive study of cross-section the lipid blood test were completed with the enzymatic-colorimetric method and additionally the abdominal girth was measured with a measuring tape of a total of 63 people. From which 71% of the studied population showed high triglyceride levels, 65% of the persons presented a high blood cholesterol, and the 75% of the men evinced a normal LDL and HDL cholesterol level. As a result of the abdominal girth from the total of 63 drivers that corresponds to the 100% of the population, 57% of them showed central obesity. Finally, relating these obese population with their lipid panel, it was found that 83% of them have high triglycerides, 75% of the people showed high cholesterol levels and the 72% of the men evinced a normal LDL and HDL cholesterol level. This results are a clearly evidence of the presence of dyslipidaemias in persons with abdominal obesity. Due to these outcomes, it is important that drivers know better how to take care of their health and moreover, they should have the information of which illnesses they are likely to develop because of the alterations of the cholesterol levels in their blood. Key words: abdominal obesity, lipid profile, lipid panel.